The delamination behaviour of Vectran/Epoxy composites having a novel non-crimp fabric architecture - Syed Abdullah, Syed Idrus Bin; Iannucci, Lorenzo; Greenhalgh, Emily S; Abdullah, Nur Azam (Elsevier Ltd, 2022)
The Mode I and Mode II Interlaminar Fracture Toughness (IFT) of Vectran/Epoxy composite material were investigated using the Double Cantilever Beam (DCB) and 4 End NotchedFlexure (4ENF) methods, respectively. Due to the relatively low compressive strength of Vectran material (<10% of its tensile properties), specimens were hybridised by overwrapping Vectran/Epoxy with T800s/M21 to prevent compressive failure during testing. Experimental results were then simulated using the non-linear Finite Element Method (FEM) package, LS-Dyna. Fractographic studies were also conducted to understand the mechanism of failure and factors influencing it.